EDUCATION ON CLEAN AND HEALTHY LIFESTYLE BEHAVIOR IN PATIH SELERA ELEMENTARY SCHOOL AS AN EFFORT TO REDUCE STUNTING RATES - Dina Rafidiyah (UMBanjarmasin, 2022)
Stunting is a serious issue in Indonesia to ensure the quality of our human resources. It is obvious that our government has taken several policies, since one out of three children in Indonesia have the prevalence to have stunting. Therefore, educating Clean and Healthy Living Behavior must be done to elementary school students in Patih Selera Village to prevent stunting. This community service was done by team from Universitas Muhammadiyah Banjarmasin. Our community service here is to educate the elementary students to wash their hand properly, to brush their teeth properly, to understand about balance nutrition and to know about family medicine herbal. Evaluation was done through observation in the class, interview with the teachers and the head master. The result is all the stake holders were happy with the community service and they hope to have the same event in the near future.